Hydro-acoustic Survey and Edge-detection method in Investigation of a Passenger Vessel Accident in East Java, Indonesia - Hendra Kurnia Febriawan; Yudo Haryadi; Aleik Nurwahyudy (Buletin Oseanografi Marina, 2020)
As an archipelagic country, the shipping sector in Indonesia becomes crucial in delivering goods inter-island, and due to increasing transportation demands. However, that industry encounters some challenges of the ocean environment that could lead to vessel accidents. An investigation into the accident is crucial since this is related to the properties, environment, and life disadvantages. The wrecks of sinking vessels also could harm the environment, providing an obstacle to the sea passage hence increasing the risk of a shipping operation. A proper and comprehensive investigation needs to be carried out to identify the factors that contribute to the accident, so then risk mitigation can be taken to prevent re-occurrence. In the case of missing foundered or sunken vessels, an underwater examination is a must, so the investigator understands the real condition of the vessel. Although diver and underwater robotic surveys are still prevalent in the investigation, these techniques have limitations due to visibility and location. By contrast, those limitations can be addressed using hydro-acoustic technologies, which are capable of providing high-resolution underwater images and digital elevation model (DEM) bathymetry. Thus, the use of these technologies is promising in-vessel accident investigation, both in-situ investigation, and post-processing analysis. This paper describes an examination of the use of side-scan sonar and multibeam echosounder in-vessel accident investigation. The use of slope feature and edge-detection technique are also investigated concerning the investigation. Results indicate that those acoustic systems can contribute to the inquiry effectively by portraying some underwater objects as the accident suspects. Besides, slope and edge detection methods also produce expectant outcomes to support underwater object detection and investigation.